Ensuring food security for every person - Singh, Tej Pal (Indian Farming, 2015)
India’s food security policy has focused essentially on increasing agriculture production by providing minimum support prices to farmers and maintaining buffer stocks of rice and wheat to ensure food security. Our country needs 265 million tonnes of cereals and 17 million tonnes of pulses by 2050. Government is committed to ensure food security for every person and several initiatives have been taken for increasing production of staple food crops of rice, wheat and pulses in a mission mode framework.